Individual and collective resources and health in Morocco - Marie-Claude Martin (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
The interaction between available individual and collective resources in the determination of health is largely ignored in the literature on the relationship between poverty and health in developing countries. We analyse the role public resources play in the perception that rural women in Morocco have of their health. These resources are taken to contribute directly and indirectly to the improvement of individual health by, on the one hand, providing a health-promoting environment and, on the other, improving the individual's ability to produce health. The empirical results of multilevel models confirm the expected associations between socioeconomic status, individual vulnerability factors and health. Furthermore, the random part of the model suggests that variation in state of health is also associated with the presence of collective resources. However, the higher the level of women's individual wealth, the less the characteristics of the community in which they live seem to be associated with their health, and the less the potential vulnerability factors seem to constrain their ability to maintain or improve health. Our results suggest that collective investments derived from various areas of activity will be more favourable to improving health, insofar as they are adapted to the initial capacity of women to benefit from them. – health ; poverty ; rural ; women ; Morocco
Keywords: H75; I19; I32; 330; Ländliches Gesundheitswesen; Marokko